Identification, Prevalence Estimation, and Mapping of Coccidiosis in Broiler Chickens (Gallus domesticus) Across Varying Elevations in Malang Regency and Batu City - Irawan, Heri; Hanifa, Filza Hannani Vawzia; Kusumarini R, Shelly; Tuska, Habib Syaiful Arif; Yesica, Reza (Universitas Airlangga, 2025)
Broiler chickens are chickens that have been specifically bred for high meat production. The increase in chicken meat consumption has become both an opportunity and a challenge for farmers, one of which is coccidiosis. Coccidiosis is caused by the Eimeria protozoa, which commonly infect chickens and target their digestive tract. This study aims to calculate the proportion and identify Eimeria species that often cause coccidiosis in broiler chickens in Malang Regency and Batu City. A total of 180 fecal samples from 6 different farms were used. The examination was conducted using the McMaster method and sporulation for 2-7 days on positive samples by immersing feces in a 2% potassium dichromate solution. Identification of Eimeria species was based on morphology and morphometry and was then were analyzed using descriptive statistics. The relationship between risk factors and coccidiosis occurrence was analyzed using Chi-square. The distribution of coccidiosis infections in Malang was depicted on an epidemiological map. The results showed that there were 4 Eimeria species infecting the six subdistricts in Malang Regency and Batu City, namely E. necatrix, E. acervulina, E. praecox, and E. maxima. The proportion of coccidiosis incidence in Malang Regency and Batu City was 18.89%. The highest proportion was in Dau District (43.33%), followed by Pagelaran District (36.67%), Kromengan District (23.33%), Wagir District (6.67%), Junrejo District (3.33%), and lastly Batu District (0%). Chi-square analysis showed that altitude and temperature had a significant effect (p<0.05) on the coccidiosis incidence rate in Malang Regency and Batu City.